EFFECT OF GRINDED OLIVE LEAVES SUPPLIMENTATION IN MILK PRODUCTION AND ITS COMPONENTS AND SOME BLOOD TRAITS IN NATIVE DOES. - & et al., AL-Musawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The present study was carried out at the Animal Farm College of Veterinary Medicine University of Baghdad during the period from 20/4/2015 to1/6/2015. This study was conducted to investigate the effect of olive leaves (grinded) supplementation to diet on milk yield, composition and some blood biochemical parameters.Ten local lactating goats and its mean initial live body weight41.38± 0.46 kg, and 2-3.5 years old were allocated according to their body weight and milk yield into two groups (5does/group). The first one (G1) was control, the second (G2) fed on diet with 2% olive leaves powder (of diet weight). The animals in both groups were fed the experimental diets 2 % DM of live body weight plus alfalfa hay (1 kg / head/day). Results showed the olive leaves powder supplementation had no significant effect on the average body weight in the end of experiment, while the milk production was significantly (P<0.05)increased in (G2) being 13.68 kg/Doe compared with 10.76 kg/Doe(G1), milk compositions (lactose. protein and fat percentage) and milk energy value did not significantly different between (G1) and (G2).Moreover blood biochemical parameters did not different in both groups. It can be concluded that olive leaves powder exerted have beneficial effects on the performance of lactating goats and no effect on blood biochemical parameters.